Pengaruh Lingkungan Rumah Terhadap Perkembangan Emosi Pada Anak Usia 0-5 Tahun - Elisa, Elisa; Nadia, Zulfa; Mahardika, I Ketut (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the influence of the home environment on emotional development in children aged 0-5 years. This research uses a literature view which is carried out by looking at several pieces of literature from other articles. The results obtained in this article are that the influence of a child's emotional development on the home environment is that initially the baby develops a sense of empathy (if he sees a friend crying, the baby will cry too), he can also feel jealous/jelusous towards other children or towards younger siblings if they already have younger siblings, Apart from that, babies can already show shyness. Several factors influence children's emotional development in their home environment, namely, the level of social activity, the child's attitude and temperament, role models from those around them.